Liberia : Interim Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note discusses the Interim Poverty Reduction Strategy Paper (I-PRSP) for Liberia. The I-PRSP traces the roots of conflict to Liberia's exclusion and marginalization of much of the population, and lays out a broad vision and program for July 2006-June 2008. It aims to consolidate peace, enhance justice, deepen democracy, ensure food security, promote human development, and steer the nation toward sustainable growth and development. The strategy reflects the many consultations the authorities held with other stakeholders.